2018
DOI: 10.3389/fendo.2018.00429
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With the Development of Nephropathy 10 Years After Diagnosis in Taiwanese Children With Juvenile-Onset Type 1 Diabetes—A Cohort Study From the CGJDES

Abstract: Objective: To examine the risk factors for diabetic nephropathy (DN) 10 years after the diagnosis of juvenile-onset type 1 diabetes mellitus (T1DM) in a Taiwanese population.Research Design and Methods: This retrospective, observational, longitudinal cohort study of 224 patients with T1DM for >10 years (mean duration 12.6 years) included participants from the Chang Gung Juvenile Diabetes Eye Study Group. The patients received a T1DM diagnosis before the age of 18 years and were treated at the pediatric endocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
(44 reference statements)
2
1
0
Order By: Relevance
“…In this study, 52.16% were female participants while 55.60% of the participants had low SES and a mean age of 15.78 ± 2.81 years, similar to previous studies in Taiwan indicating 52.5% of TID adolescents were female, 42.9% were low SES, and having a mean age of 14.90 ± 2.46 years (Lee et al, 2020). The mean BMI was 20.82 ± 3.41 kg/cm 2 in this study, which was similar to 20.1 ± 2.8 kg/cm 2 in the study of Yang et al (2018). Of our participants, 71.6% had 6‐month HbA1c levels higher than 7.5%, which was consistent with 81.9% in a previous study in Taiwan (Lee et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, 52.16% were female participants while 55.60% of the participants had low SES and a mean age of 15.78 ± 2.81 years, similar to previous studies in Taiwan indicating 52.5% of TID adolescents were female, 42.9% were low SES, and having a mean age of 14.90 ± 2.46 years (Lee et al, 2020). The mean BMI was 20.82 ± 3.41 kg/cm 2 in this study, which was similar to 20.1 ± 2.8 kg/cm 2 in the study of Yang et al (2018). Of our participants, 71.6% had 6‐month HbA1c levels higher than 7.5%, which was consistent with 81.9% in a previous study in Taiwan (Lee et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The mean value of HbA1c in patients' with complications was 9.63% indicating poor control of diabetes. These findings are in accordance with previous studies by Yang et al (26) , Bjornstad et al (27) , and Lind et al (28) who reported that long diabetes duration, poor glycemic control and hypertension are risk factors for the development of microvascular complications as diabetic nephropathy. Moreover, there was significantly statistically difference between patients subgroups regarding cholesterol, which was increased in complicated patients (p = 0.001).…”
Section: Il29supporting
confidence: 93%
“…Structural changes may be observed in kidney biopsies as early as the first few years after the onset of diabetes, but the disease has a long “silent period” in its development ( 18 ). Thus, our current understanding of the trajectory of DN in children and adolescents suggests that advanced CKD and kidney failure take decades to develop after the onset/diagnosis of diabetes, which means that the data on the prevalence and time course of these outcomes in childhood-onset diabetes is largely derived from adult studies ( 19 , 20 ). This presents a dilemma for any rigorous study of diabetic kidney disease (DKD) in children and adolescents because understanding any aspect of DN, for example biomarkers, risk factors for progression, and assessment of response to interventions, has had to rely on intermediate outcomes, such as albuminuria, and hyperfiltration.…”
Section: Discussionmentioning
confidence: 99%